2014
DOI: 10.1021/ml500322h
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Facilitated Cryoprotection of Viruses

Abstract: Global vaccination and gene therapy programs have an urgent demand for stabilization of viral vectors at low temperature. We used a quadramer, a bridge-connected DNA tetra-aptamer to antivesicular stomatitis virus (VSV), as a viral cryoprotectant. Results showed that the tetravalent antivirus DNA aptamers protect viral activity during multiple freeze− thaw cycles, shield from neutralizing antibodies, and decrease aggregation of viral particles.KEYWORDS: Aptamer, quadramer, vesicular stomatitis virus, viral sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Moreover, the aptamers rarely induce immune response. They have been applied in a number of applications including antivirus (Ghobadloo et al, 2014) anticancer (Ireson and Kelland, 2006) and drug delivery (Zhang et al, 2011). Previously, our study has demonstrated that using PDGF-BB aptamer to interfere with the binding of PDGF-BB to its receptor suppressed CRC cell proliferation in part via down-regulation of the Ras/Raf/MEK/ERK signaling pathway (Sae-Lim et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the aptamers rarely induce immune response. They have been applied in a number of applications including antivirus (Ghobadloo et al, 2014) anticancer (Ireson and Kelland, 2006) and drug delivery (Zhang et al, 2011). Previously, our study has demonstrated that using PDGF-BB aptamer to interfere with the binding of PDGF-BB to its receptor suppressed CRC cell proliferation in part via down-regulation of the Ras/Raf/MEK/ERK signaling pathway (Sae-Lim et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…However, the Influenza A virus was much more susceptible, with one log reduction in infectivity after two cycles of freezing at –40 °C and thawing for 20 min at room temperature, and a seven log reduction after five cycles [34]. In the case of Vesicular stomatitis virus (VSV), infectivity declined by two log values after 10 freeze–thaw cycles but the precise conditions were not specified [35]. Therefore, it appears that the MV is more robust than the Influenza A virus and VSV with respect to the damage caused by freeze–thaw cycles, which is advantageous for the preparation of the virus particles.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of oncolytic viruses induces neutralizing antibodies (nAbs) production, decreasing the antitumor effect [ 97 ]. At the proof-of-concept level, novel methods for OVs shielding from nAbs have been proposed [ 49 , 50 , 98 ]. The antigen-binding fragment (Fab) region of the rabbit anti-vesicular stomatitis virus (VSV) neutralizing polyclonal antibodies was chosen as the target for aptamer selection.…”
Section: Applications Of Aptamersmentioning
confidence: 99%
“…In the works mentioned above [ 49 , 50 , 98 ], DNA-aptamer selection against VSVs was also carried out. It was shown that the combination of anti-VSV and anti-nAbs aptamers resulted in increased infectivity, indicating a synergistic mechanism.…”
Section: Applications Of Aptamersmentioning
confidence: 99%
See 1 more Smart Citation